Use of Cornelian cherry, hawthorn, red plum, roseship and pomegranate juices in the production of water kefir beverages. (August 2021) - Ozcelik, Ferhat; Akan, Ecem; Kinik, Ozer
Abstract: In this study, fruit juices of Cornelian cherry, hawthorn, red plum, roseship and pomegranate were fermented with water kefir grains for 48 h at 25 °C. The physicochemical, microbiological, sensorial properties, and total phenolic compound content and antioxidant (2, 2-Diphenyl-1-picrylhydrazyl (DPPH) method) activities of water kefir beverages were determined during 28 day of storage. It was determined that the pH value of all beverages ranged from 3.45 to 3.97 at the end of fermentation. Rosehip and pomegranate beverages had the highest total phenolic compound and DPPH radical scavenging activity during the storage period (p < 0.05). During the storage period, the highest Lactobacillus spp., and Lactococcus spp. counts were determined in rosehip beverage. Water kefir beverages from pomegranate and roseship more preferred by panelists. In this research, it has been concluded that fruit juices can be used in the production of water kefir and the functionality of the produced beverages can be increased.